Aluminum-induced decrease in CO2 assimilation in 'Rangpur' lime is associated with low stomatal conductance rather than low photochemical performances - Banhos, Otavia F.A.A. [UNESP]; de O. Carvalho, Brenda M.; da Veiga, Eduardo B. [UNESP]; Bressan, Anna C.G. [UNESP]; Tanaka, Francisco A.O.; Habermann, Gustavo [UNESP] (Elsevier, 2016)
Aluminum (Al) is toxic to most plants. Although inhibition of root elongation can occur even under 10 μM Al, above 1000 μM damage to photochemical performances has been reported, reducing the CO2 assimilation rate (A). However, Al is retained in the roots of most plants, including Citrus limonia ('Rangpur' lime) with no direct explanation for the low A. In this study, 'Rangpur' lime plants were cultivated hydroponically in a nutrient solution with 1480 μM Al, and we expected to determine the time range within which Al-induced decrease in A starts. To our surprise, low stomatal conductance (gs) rather than low photochemical performances was evident 45 days after exposing the roots to Al. Aluminum was mostly retained in the roots and histochemically observed in the stele, suggesting reduction in water uptake/transport in the xylem that became fibrous. We also found a 35% reduction in the midday leaf water potential in plants exposed to Al, indicating association between the fibrous xylem vessels and low gs, which could explain the Al-induced decrease in A in 'Rangpur' lime plants.
Keywords: Aluminum allocation; Citrus limonia; Histochemical characteristics; Leaf gas exchange parameters; Long-distance Al effects